Creed & grievance : Muslim-Christian relations & conflict resolution in northern Nigeria - Mustapha, Abdul Raufu; Ehrhardt, David, 1982- (Western Africa series., 2018)
In northern Nigeria, high levels of ethnic diversity have coincided with acute polarization between Muslims and Christians, increasingly fuelling violent conflict. The climate of insecurity threatens northern Nigeria's development, accentuates the inequalities between it and the rest of the country, and undermines the attempt to stabilize democracy in the country. Externally, fears have also been expressed that Islamist movements in northern Nigeria form part of a wider network constituting a threat to global peace and security. Refuting a "clash of civilizations" between Muslims and Christians, the authors of this new study highlight the multiplicity of Muslim and Christian groups contending for influence and relevance, and the doctrinal, political and historical drivers of conflict and violence between and within them. They analyse three of the most contentious issues: the conflicts in Jos; the Boko Haram insurgency; and the challenges of legal pluralism posed by the declaration of full Sharia law in 12 Muslim majority states. Finally, they suggest appropriate and effective policy responses at local, national and international levels, discussing the importance of informal institutions as avenues for peace-building and the complementarities between local and national dynamics in the search for peace. Abdul Raufu Mustapha is Associate Professor in African Politics, University of Oxford. David Ehrhardt is Assistant Professor of International Development at Leiden University College. Companion volume: Sects & Social Disorder: Muslim Identities & Conflict in Northern Nigeria edited by Abdul Raufu Mustapha, (James Currey 2014)